The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1210/jc.2013-1222
|View full text |Cite
|
Sign up to set email alerts
|

GH Treatment to Final Height Produces Similar Height Gains in Patients With SHOX Deficiency and Turner Syndrome: Results of a Multicenter Trial

Abstract: GH treatment in short children with SHOX deficiency showed similar long-term efficacy as seen in girls with Turner syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
67
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 40 publications
7
67
0
6
Order By: Relevance
“…A SHOX gén homozigóta eltérése a Langerszindrómát (LS) eredményezi, amely egy rendkívül ritka és súlyos tünetegyüttes, jelentős növekedési elmaradással és az ulna, illetve fibula hypo-és/vagy aplasiájával társul. Génmultiplikáció esetén, például Klinefelter-szindrómá-ban (a nemi kromoszómák triszómiája, rendszerint 47,XXY karyotypussal) a betegekre általában a magas termet jellemző, alátámasztva részben a SHOX növeke-désre kifejtett dózisfüggő hatását [12].…”
unclassified
“…A SHOX gén homozigóta eltérése a Langerszindrómát (LS) eredményezi, amely egy rendkívül ritka és súlyos tünetegyüttes, jelentős növekedési elmaradással és az ulna, illetve fibula hypo-és/vagy aplasiájával társul. Génmultiplikáció esetén, például Klinefelter-szindrómá-ban (a nemi kromoszómák triszómiája, rendszerint 47,XXY karyotypussal) a betegekre általában a magas termet jellemző, alátámasztva részben a SHOX növeke-désre kifejtett dózisfüggő hatását [12].…”
unclassified
“…This multinational, prospective, open-label, randomized study was conducted at 33 study sites in 14 countries and comprised three periods [24]: (i) screening for eligible patients including DNA analysis for SHOX gene mutations/deletions, (ii) a 2-year randomized control period [18] and (iii) an extension to final height (FH) or study closure [24]. Patients with confirmed SHOX deficiency were randomized to the GH treatment group (n = 27) or the non-treatment control group (n = 25).…”
Section: Study Design/patientsmentioning
confidence: 99%
“…Enrolled subjects were evaluated at baseline (at the start of GH treatment [24]) for standing height and pre-existing conditions. Subsequent evaluation was performed after 3 months and 1 year of treatment.…”
Section: Clinical and Biochemical Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Short stature homeobox-containing gene (SHOX) deficiency is a licensed indication for GH therapy and it has been shown that GH therapy increases short-and long-term height prognosis in these patients [7].…”
mentioning
confidence: 99%